1998
DOI: 10.1046/j.1365-3040.1998.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of light on induction, time courses, and kinetic patterns of net nitrate uptake in barley

Abstract: Barley seedlings (Hordeum vulgare L.) were grown hydroponically with (induced) or without (uninduced) nitrate in a light/dark cycle with high photon flux density to determine the effects of light on time courses, induction and kinetics of net nitrate uptake. Nitrate uptake was induced by external nitrate in both light and dark and was prevented by 1 mol m -3 p-fluorophenylalanine. In high light, nitrate uptake was about 2-fold higher than in low light. During time course experiments the uptake rates oscillated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
5
18
1
Order By: Relevance
“…Nutrients can be transferred from the phloem into the xylem, which results in circulation of most of the nutrients. Exceptions are Ca 2+ and NO 3 ) (Peuke and Jeschke 1998), which are almost phloem-immobile. In wheat and rice, more than 60% of the amino-N and 26% and 36% respectively of K + in the xylem originates from the phloem (Grignon and Sentenac 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients can be transferred from the phloem into the xylem, which results in circulation of most of the nutrients. Exceptions are Ca 2+ and NO 3 ) (Peuke and Jeschke 1998), which are almost phloem-immobile. In wheat and rice, more than 60% of the amino-N and 26% and 36% respectively of K + in the xylem originates from the phloem (Grignon and Sentenac 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the change in nutrient absorption rates throughout the day has been one of the most frequently researched topics, and it was found that the daily changes in absorption rates follow different patterns: a single peak during the daytime (Adams, 1980;Keltjens and Nijenstein, 1987;Pearson and Steer, 1977) or double peaks, one in the daytime and another in the nighttime (Hansen, 1980;Le Bot and Kirkby, 1992;Pan et al, 1987;Peuke and Jeschke, 1998;Steingröver et al, 1986). Currently, these different absorption patterns are explained by the variations in growth conditions maintained during experiments, such as those in a greenhouse versus those in an artificial climate room.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, nitrate uptake increases 20% to 40% within a few hours and then becomes steady when plants are transferred from dark to light in barley [4] and decreases by a similar amount on transfer from light to dark in tobacco and soybean [5,6]. In prolonged darkness, the nitrate uptake rate may subsequently decline even further [7,8]. In tomato the initial adjustment of nitrate uptake takes longer, increasing in the light and decreasing in darkness continuously over a period of 6 h or more [9].…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of nitrate uptake with a time resolution of minutes are therefore needed. However, in most published work on nitrate responses to light, time courses have generally been measured with relatively few points, none less than 1 h apart, and often after 4 or 6 h. Peuke and Jeschke have provided systematic time courses with more frequent measurement, but a lag of the order of minutes would not be visible in their system because of the variability of the measured uptake rates [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation